2014
DOI: 10.1074/jbc.m113.536888
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cysteine-scanning Mutagenesis Reveals Claudin-2 Pore-lining Residues with Different Intrapore Locations

Abstract: Background:The composition of the claudin paracellular pore region is incompletely known. Results: Cysteine-scanning mutagenesis of the first extracellular domain of claudin-2 was used to identify all pore-lining residues and their intrapore locations. Conclusion: This study maps out the claudin-2 pore region. Significance: This advances understanding of the structure-function relationship of claudin pores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…The first extracellular loop (ECL1) of claudin proteins contains several conserved sequences, and most claudins also include a carboxy-terminal PDZ-binding sequence that interacts with the PDZ1 domain of ZO proteins (Itoh et al 1999). It is well-documented that many claudin proteins form paracellular pores, and that the charge selectivity of these pores is defined by amino acids within ECL1 (Colegio et al 2003; Li et al 2014; Weber et al 2015). The relationship of this to health and disease was initially shown by genetic linkage of para-cellin-1, or claudin-16, to the autosomal recessive disease of renal hypomagnesemia with hypercalciuria and nephrocalcinosis (Simon et al 1999).…”
Section: Tight Junction Molecular Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…The first extracellular loop (ECL1) of claudin proteins contains several conserved sequences, and most claudins also include a carboxy-terminal PDZ-binding sequence that interacts with the PDZ1 domain of ZO proteins (Itoh et al 1999). It is well-documented that many claudin proteins form paracellular pores, and that the charge selectivity of these pores is defined by amino acids within ECL1 (Colegio et al 2003; Li et al 2014; Weber et al 2015). The relationship of this to health and disease was initially shown by genetic linkage of para-cellin-1, or claudin-16, to the autosomal recessive disease of renal hypomagnesemia with hypercalciuria and nephrocalcinosis (Simon et al 1999).…”
Section: Tight Junction Molecular Architecturementioning
confidence: 99%
“…Further, whereas the MLCK inhibitor PIK can reverse TNF-induced barrier loss, it is ineffective against IL-13-induced barrier loss (Weber et al 2010). The latter is explained by the observation that IL-13 augments paracellular permeability by increasing claudin-2 expression (Heller et al 2005; Weber et al 2010), which has been shown to create paracellular cation-selective pores (Furuse et al 2001; Amasheh et al 2002; Li et al 2014; Weber et al 2015). Intriguingly, claudin-2 is selectively upregulated by IL-13 (Weber et al 2010), whereas other stimuli regulate expression of multiple tight junction-related proteins.…”
Section: Il-13-mediated Regulation Of Tight Junction Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Claudin-2 pores also permit the flux of water through a common pore (Muto et al, 2010;Rosenthal et al, 2016Rosenthal et al, , 2010. The specificity for Na + is governed by the first of two extracellular loops of claudin-2 that are adjoined to four transmembrane domains with intracellular N-and C-termini Li et al, 2014;Suzuki et al, 2014;Yu et al, 2009). Pore-forming claudins define the charge and size selectivity of the high-capacity pore pathway Colegio et al, 2002;Shen et al, 2011;Turner, 2009;Van Itallie et al, 2008;Weber et al, 2010).…”
Section: Claudin Proteins Define the Selectivity Of Paracellular Permmentioning
confidence: 99%
“…13,14 Additional porelining residues were identified in a study using cysteine-scanning mutagenesis and thiol group modification including, from the narrowest to the widest part of the pore, S68, S47, T62/I66, T56, T32/G45, and M52. 15 Pore-lining residues from D65 to S68 in the ECL1 are believed to be the most important ones for the paracellular functions of claudin-2, and the negatively charged D65 is already known to be determinative for cation selectivity. 11,12 Additionally, through electrostatic interactions with D65 12 and weaker interactions with negatively charged p-electrons of the Y67 aromatic residue 16 , cations are able to permeate the pore in a dehydrated or partially dehydrated state.…”
Section: Introductionmentioning
confidence: 99%